Uniform Spinning Sampling Gradient Electron Paramagnetic Resonance Imaging - Johnson, David H. (2014)
PURPOSE: To improve the quality and speed of electron paramagnetic resonance imaging (EPRI) acquisition by combining a uniform sampling distribution with spinning gradient acquisition. THEORY AND METHODS: A uniform sampling distribution was derived for spinning gradient EPRI acquisition (Uniform Spinning Sampling, USS) and compared to the existing (Equilinear Spinning Sampling, ESS) acquisition strategy. Novel corrections were introduced to reduce artifacts in experimental data. RESULTS: Simulations demonstrated that USS puts an equal number of projections near each axis whereas ESS puts excessive projections at one axis, wasting acquisition time. Artifact corrections added to the magnetic gradient waveforms reduced noise and correlation between projections. USS images had higher SNR (85.9±0.8 vs. 56.2±0.8) and lower mean-squared error than ESS images. The quality of the USS images did not vary with the magnetic gradient orientation, in contrast to ESS images. The quality of rat heart images was improved using USS compared to that with ESS or traditional fast-scan acquisitions. CONCLUSION: A novel EPRI acquisition which combines spinning gradient acquisition with a uniform sampling distribution was developed. This USS spinning gradient acquisition offers superior SNR and reduced artifacts compared to prior methods enabling potential improvements in speed and quality of EPR imaging in biological applications.